The quest of finding the CSR rationale in the 21st century - Klomps, Dennis Richard (2017)
Corporate Social Responsibility (CSR) is a topic that proved to have become increasingly relevant from the 1990s onwards, from both an academic as well as a business perspective. The aim of this Thesis is to discover what drives nowadays’ companies into CSR. This research goal is divided in three research questions which cover (non)financial intra-firm-, awareness-, and governmental (regulatory) aspects of CSR. The research questions are answered through literary research (containing underlying philosophical theories, levels of analysis, the history, strategic concepts, and (non)financial pros and cons of CSR) and qualitative interviews with CSR-representatives (demonstrating supportive, complementary, and opposing views towards existing literature). The aggregated findings are that CSR is not only performed to boost other intra-company aspects besides company image, that CSR would be performed if it would not be communicated outside the company itself, and that CSR does not only exist because governments and other institutions fail to intervene and/or regulate at appropriate levels.